Vulnerability and adaptive capacities to slope failure threat: a study of the Klang Valley region - Thanapackiam, P. (Springer Verlag (Germany), 2012)
This article examines the relationship between vulnerability and adaptive capacities of urban dwellers to slope failure threats. The Klang Valley Region in Peninsular Malaysia was selected as the study area based on the increasing frequency and impact of slope failures in the last decade. The study identified, examined, and mapped 10 slope failure locations, and the vulnerability characteristics of urban dwellers staying in areas that are prone to and threatened by slope failures were described. The identified vulnerability indicators are related to factors such as (1) socio-economic status, (2) population,(3) external characteristics, (4) physical structure of dwellings, and (5) adaptation measures. Finally, the perceptions of the residents who are at risk of slope failure hazards and their inherent coping mechanisms were analyzed. A model describing the relationships among slope failure threats, vulnerability of urban dwellers, and their adaptive capacities was formulated.